IMPLEMENTATION OF GRAMEEN BANK PATTERNS IN INCREASING AND STRENGTHENING THE MIDDLE ECONOMIC SECTOR POST-ERUPTION OF KELUD MOUNTAIN - Fuddin, Muhammad Khoirul (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
The natural disasters of the Mount Kelud eruption that occurred in Malang Regency in 2014 had a negative impact on the economic conditions and the level of welfare of the communities affected by the eruption. After the eruption of Mount Kelud as a large part of the community that became victims will begin the condition of their economic activities starting from the beginning considering that most of the capital and production factors owned have been damaged and destroyed by the eruption. Meeting capital requirements is a major problem in starting the economic activities of the surrounding community. Capital adequacy by making loans to banking institutions is considered difficult by the community because the community is considered not bankable by financial institutions. The research methodology used in this study is to use descriptive methods by using literature review from various sources and data. The results of this study conclude that the capital shortcomings and difficulties experienced by the surrounding community after the Mount Kelud eruption can be overcome by implementing the Grameen Bank pattern, where the pattern is considered effective and in accordance with the conditions and attitudes of the community that uphold mutual cooperation and family values because of the Grameen Bank pattern adhering to a joint responsibility system.